African Swine Fever Virus Multigene Family Genes Inhibit the Type-I Interferon Response by Acting on the NFκB and IRF3 Signalling Pathways at the Transcription Factor Level or below - Samuel Connell; Ana Reis; Anusyah Rathakrishnan; Sarah Gilbert; Linda Dixon (Proceedings, 2020)
African Swine Fever Virus (ASFV) is a haemorrhagic infection of swine, which routinely displays 100% lethality. [...]